Religious Moderation With The Support Of Islamic Religious Education - M. Aditya Ramdhani; Abdul Aziz Romdhoni (MAQOLAT: Journal of Islamic Studies, 2023)
Indonesia is a country that has many ethnic groups, races and religions. The diversity that Indonesia has can be a benchmark for how harmony occurs and how people's attitudes accept differences and interact directly with the cultures of different communities. So it is necessary to implement and understand religious moderation for multicultural nations. Religious moderation as a middle way to deal with extreme and fundamental group differences. The method applied as the existing material is socio-religious, namely a social approach and infused with religion. Through this moderate-based religious education, it is hoped that the millennial generation can uphold the basics of religion, thereby minimizing conflict and triggering violence in the name of religion. Apart from the above, the momentum to strengthen correct, tolerant understanding can be realized through moderate-based religious education. This was done to emphasize that the slanted accusations against Islam are not true and are not Islamic teachings. Islam is a religion that is rahmatan lil'alamin which teaches preaching with the principles of peaceful messages. In this way, extreme and harsh preaching messages are not part of moderate Islamic education.